Analisis Biaya Standar Sebagai Alat PengendalianBiaya Tenaga Kerja Langsung pada PT Masaiki Jakarta - Suryani, Rani; Srisulistiowati, Dwi Budi (Journal of Informatic and Information Security, 2021)
The standard setting of wage rates based on the ability of business entities or agreements between workers and business entities as well as the average wage of workers in the past, efficiency standards are set by looking at the actual performance of a worker. The research methods used in this research are descriptive with a quantitative approach. The research data used in this study is secondary data. Data sources that do not directly provide data to data collectors, The difference in direct labor costs that occur in PT Masaiki is profitable. Although variance is beneficial in controlling direct worker costs is not necessarily a maximal profitable variance, But if the business entity uses the budgeted costs with continuous difference analysis in controlling direct worker costs, the direct worker costs that must be used by business entities will be small and small costs will increase profits so that optimal profits will be obtained by business entities.